The inverse scattering problem for the Jacobi operator - Martínez Macedonio, Edgar (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
We explore the solution to the scattering problem for the Jacobi operator on the half-line with the Dirichlet boundary condition. Based on the work Inverse problems in scattering theory for second-order self-adjoint difference operators, PhD Thesis in Russian, Lomonosov Moscow State University, 1976 by G. Sh. Guseinov, we study the reconstruction of the Jacobi operator from the scattering data. Among others, we also refer the paper Inverse problem with transmission eigenvalues for the discrete Schrödinger equation, Journal of Mathematical Physics 56 (2015), 082101 by T. Aktosun and V. G. Papanicolaou. Chapter 1 focuses on deriving scattering data from direct problems, while Chapter 2 develops the solution to the inverse scattering problems.

Exploramos la solución al problema de dispersión para el operador de Jacobi en la semirrecta con la condición de frontera de Dirichlet. Basándonos en el trabajo Inverse problems in scattering theory for second-order self-adjoint difference operators, Tesis Doctoral en ruso, Universidad Estatal de Moscú Lomonósov, 1976, de G. Sh. Guseinov, estudiamos la reconstrucción del operador de Jacobi a partir de los datos de dispersión. Entre otros, También hacemos referencia al artículo Inverse problem with transmission eigenvalues for the discrete Schrödinger equation, Journal of Mathematical Physics 56 (2015), 082101, de T. Aktosun y V. G. Papanicolaou. El Capítulo 1 se centra en la obtención de datos de dispersión a partir de problemas directos, mientras que el Capítulo 2 desarrolla la solución a los problemas inversos de dispersión.
Instituto de Física y Matemáticas. Facultad de Ciencias Físico Matemáticas. Unidad Morelia del Instituto de Matemáticas de la UNAM. Programa Conjunto de Maestría en Matemáticas
Keywords: info:eu-repo/classification/cti/1; IFM-M-2025-0288; Operador de Jacobi; Dispersión; Espacios de Hilbert; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19249